A CASE REPORT ON GIANT CAROTID − OPHTHALMIC ARTERY ANEURYSM - Stanojević, Bojan; Ilić, Jovan; Nikolov, Vesna; Aracki-Trenkic, Aleksandra; Jelenković, Boban; Živković, Slavko; Đorđević, Marija; Todorović, Stefan (Acta medicae Medianae, 2022)
Ophthalmic artery (OA) is a potential origin of aneurysms. We present a patient with a giant OA aneurysm, with a sudden onset of psychomotor agitation at the admission. Digital subtraction angiography showed an aneurysm originating from the ophthalmic segment of the left internal carotid artery of irregular shape, with diameters up to 6.5 x 4.5 mm, while the neck of the aneurysm was 4 mm wide. On computed tomography angiography, the aneurysm was seen as much larger and round, up to 4.7 cm in diameter and with a calcified wall. In the further course of treatment, the microcatheter was placed in the lumen of the aneurysm and the embolization spirals were set within. This resulted in a complete exclusion of the aneurysm from the circulation. Endovascular treatment for the giant OA aneurysm, such as coil embolization technique, might be successful for the complete exclusion from circulation of a giant and partially thrombosed aneurysm.